Development of a Software Tool for Visualizing a Mine (Wellbore) in the Industrial Drilling of Oil Wells; Processes; Vol. 11, iss. 2 - Abu-Abed F. Fares; Pivovarov K. D. Kirill Dmitrievich; Zhironkin V. S. Vitaly Sergeevich; Zhironkin S. A. Sergey Aleksandrovich (2022, 2022)
Title screen